2017
DOI: 10.2147/opth.s136882
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the refractive outcome and accuracy of IOL power calculation after phacoemulsification using the SRK/T formula with ultrasound biometry in medium axial lengths

Abstract: PurposeTo evaluate the accuracy of the SRK/T formula using ultrasound (US) biometry in predicting a target postoperative refraction of ±1.00D in eyes with medium axial length (AL) that underwent phacoemulsification.MethodsThe present study was a retrospective analysis, which included 538 eyes with an AL from 22.0 to 24.60 mm that underwent phacoemulsification and foldable intraocular lens (IOL) implantation (six different IOLs) in the bag. Preoperative AL was measured by US biometry and IOL power (IOLp) was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 30 publications
3
16
0
Order By: Relevance
“…In this study by using the SRK/T formula, the mean numeric error ranged from −1.38 D to +1.34 D. The mean error was -0.08 ± 0.61 D. The majority of patients (90%) were within 1 D of the predicted refractive error (Table 2). These results were similar to the study done by Karabela et al (3) with a prediction accuracy of 38.66% for refractive errors of 0.25D, 69.51% for refractive errors of 0.50D, and 93.87% for refractive errors of 1.00D. Lagrasta et al (9) showed a prediction accuracy of 55% for refractive error within 0.50D, and 91% for refractive error within 1.00D using SRK/T formula with US biometry in 33 eyes of 33 patients with medium ALs (22.2-24.5 mm).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study by using the SRK/T formula, the mean numeric error ranged from −1.38 D to +1.34 D. The mean error was -0.08 ± 0.61 D. The majority of patients (90%) were within 1 D of the predicted refractive error (Table 2). These results were similar to the study done by Karabela et al (3) with a prediction accuracy of 38.66% for refractive errors of 0.25D, 69.51% for refractive errors of 0.50D, and 93.87% for refractive errors of 1.00D. Lagrasta et al (9) showed a prediction accuracy of 55% for refractive error within 0.50D, and 91% for refractive error within 1.00D using SRK/T formula with US biometry in 33 eyes of 33 patients with medium ALs (22.2-24.5 mm).…”
Section: Discussionsupporting
confidence: 93%
“…Accurate biometric data are essential for achieving good surgical outcomes and patient satisfaction after cataract and refractive surgery. Third-generation formulas such as the Holladay 1, the Hoffer Q, and the SRK/T; fourth-generation formulas such as the Holladay 2, the Haigis, and the Olsen; and newer formulas are the most commonly used in all eyes (3) . Different studies to evaluate the predictive accuracy of various IOL power calculation formulas; Wang et al (6) showed similar performance of the Haigis, Hoffer Q, Holladay1, and SRK/T in medium eye length, in another study SRK/T and Haigis performed equally well and outperformed the Hoffer Q and Holladay 1 in 34 eyes between 25 and 28mm (7) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a multicentre, prospective cohort study involving 1553 eyes, Hahn et al reported that 95% achieved a 1-month postoperative refraction within 1 D of target 9. Karabela et al reported a relatively high refractive success of 93% of patients being within 1 D of target refraction 10. However, these results were in selected populations.…”
Section: Discussionmentioning
confidence: 99%
“…Hahn et al excluded patients with any ocular comorbidity or previous eye surgery; lenses used were only in the range of +16 to+26 to avoid possible pitfalls in predicting refraction at the low and high ends of the refractive spectrum, all patients were suitable for optical biometry, and all of the operating surgeons were highly experienced in cataract surgery having previously performed over 10 000 cases 9. Similarly, Karabela et al only included patients with medium AL ranging from 22.00 to 24.60 mm in their study 10. The Swedish National Cataract Register Study, which included 17 056 operations, reported 92.70% of cases to be within 1 D of target refraction 1–2 months postoperatively 12.…”
Section: Discussionmentioning
confidence: 99%